El muralismo urbano y su dispositivo disensual: una aproximación desde Jacques Ranciére (2016)
This text will examine artistic practices associated with images and that take place in contemporary urban contexts, which constitute an exercise in the material and symbolic reconfiguration of public spaces. The objective is to determine how these artistic practices are used through actions that have political repercussions. It thus establishes the principal differences between some manifestations of urban art, such graffiti and monumental art as well as what has been called urban muralism, in order to establish the particular features of the latter and highlight its nature and the way it problematizes certain sensory frontiers. This characterization will make it possible to elucidate how urban muralism enables the ownership and resignification of the territory by citizens who discover in the arts both a channel for their own voice and a pathway for questioning the social structure that makes them invisible.